2022
DOI: 10.7759/cureus.29228
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Obesity, Willingness to Lose Weight, and Treatment Preferences Among Overweight and Obese Saudi Adults

Abstract: Background: Obesity has become a major health concern worldwide and is associated with several diseases and complications. Losing weight is an effective strategy to improve body mass index and prevent the complications of obesity. However, weight loss is dependent on the attitude of individuals toward obesity as well as their willingness to lose weight.Aim: To explore attitudes toward obesity, willingness to lose weight, and treatment preferences among overweight and obese Saudi adults.Methods: An analytical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A study on severely obese children and adolescents in the United States, 1999-2012 reported that the prevalence of high TC, low HDL, high triglycerides, high LDL among severely obese adolescents was 16.5%, 40.0%, 30.0%, 13.0%, respectively [22]. A study on obese children in Saudi Arabia found that overweight children had higher HDL levels, while obese children had higher TG levels [23]. In the present study, we found that there were signi cant difference of TG, TC, HDL-C, LDL-C and dyslipidemia prevalence among children and adolescents with or without obesity/overweight.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%
“…A study on severely obese children and adolescents in the United States, 1999-2012 reported that the prevalence of high TC, low HDL, high triglycerides, high LDL among severely obese adolescents was 16.5%, 40.0%, 30.0%, 13.0%, respectively [22]. A study on obese children in Saudi Arabia found that overweight children had higher HDL levels, while obese children had higher TG levels [23]. In the present study, we found that there were signi cant difference of TG, TC, HDL-C, LDL-C and dyslipidemia prevalence among children and adolescents with or without obesity/overweight.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%